THE CONSUMER BEHAVIOUR AND NEW BRAND MANAGEMENT POLICIES OF ORGANIC FOOD IN ITALY: THE CASE STUDY OF “VIVI VERDE COOP” - Marchese, Aldo; Masotti, Matteo; Sidali, Katia Laura; Dörr, Andrea Cristina (Ciência e Natura, 2014)
http://dx.doi.org/10.5902/2179460X11269 Due to economic growth, social, cultural and demographic changes lead to changes on food production patterns. Increased instruction levels, strong urbanization and consequent depopulation of rural areas, increased number of working women, increased wealth of families, growth and differentiation of food demand led to deep innovations in consumers priorities and choices. It means that consumption behaviors are now more focused on food safety (search for secure, healthy and even biological food) rather than food security (the problem of food scarcity no longer affects the developed countries). Food producers and distributors, in particular large scale distribution, gradually adapted their strategies to meet the emerging consumers’ preferences. In this paper we analyze the brand management strategy “ViviVerde” pursued by Coop and, also we perfom an analysis of the demand elasticity of the food products sold with the ViviVerde label (eggs, milk, fresh cheese, pasta, fruit juices) from de period of January 2010 to May 2012 in the Italian Province of Bologna. The conclusions are that economic performance of a line of products of the ViviVerde Coop, that clearly pursues the Corporate Social Responsibility objectives, is positive and increasing. It demonstrates that those kinds of brand management strategies can be successful.